Regulating tobacco - Rabin, Robert L.; Sugarman, Stephen D. (Oxford University Press, 2001)
This collection includes essays by 11 leading public health experts, economists, physicians, political scientists, and lawyers, whose activities encompass Congressional testimonies, Surgeon General's reports on youth smoking, and clinical trials for drugs for smoking cessation. They analyze specific strategies that have been used to influence tobacco use, including taxation, regulation of advertising and promotion, regulation of indoor smoking, control of youth access to cigarettes and other tobacco products, litigation, and subsidies of smoking cessation, and set them against the scientific findings about tobacco and the changing cultural and political setting against which policy decisions are being made.; This book is intended for scholars, lawyers, policy-makers, anti-tobacco activists, those interested in the development of tobacco regulations.